True cost of food and land degradation - Alisher Mirzabaev; Joachim von Braun (Russian Journal of Economics, 2022)
Achievement of Sustainable Development Goals critically depends on well-functioning food systems which can provide sufficient and healthy food for all in an environmentally sustainable, economically viable and socially equitable manner. However, current food systems are failing on all of these dimensions. In fact, food systems are generating substantial amounts of environmental, health-related, social, and economic externalities negatively affecting the well-being of present and future generations of people, particularly that of the poorest and most vulnerable. True cost accounting approaches, a research frontier in sustainability sciences, seek to comprehensively measure these so far unaccounted externalities from food systems to propose solutions for addressing their negative social welfare effects. Contributing to discussions on true costs of food, this paper traces the environmental costs of ecosystems degradation due to cropland expansion during the period of 2001 to 2009 at the global level. The results show that cropland expansion caused by growing food demands has led to the degradation of 511 million hectares of higher value forest, woodland, shrubland and grassland ecosystems globally, with the total economic costs equaling 435 billion U.S. dollars. This means that each year the global community is incurring 54 billion U.S. dollars of externality costs from food systems because of cropland expansion alone. Addressing this problem requires a flexible government regulation combining incentive mechanisms such as payments for ecosystem services and carbon pricing, with legislative deterrents, e. g., environmentally friendly cadastral planning, fines, and taxes. Current research on true cost accounting is primarily focused on identifying the extent of externalities from food systems. However, knowledge does not always automatically translate into action. The key impetus for future actions for true pricing of food would come from closing knowledge gaps on transaction costs for the implementation of true pricing and the development of innovative solutions for reducing them.